Implementation Of Oral Hygiene Using 0.2% Chlorhexidine Gluconate To Reduce The Risk Of Ventilator-Associated Pneumonia In Mechanically Ventilated Patients With Pneumonia In The Intensive Care Unit: A Case Study - Pipin Anita; Maria Astrid (CV. AFDIFAL MAJU BERKAH, 2026)
Ventilator-Associated Pneumonia (VAP) is one of the most common healthcare-associated infections in critically ill patients receiving mechanical ventilation for more than 48 hours. Bacterial colonization of the oral cavity and oropharynx contributes significantly to the development of VAP through microaspiration. Oral hygiene using 0.2% chlorhexidine gluconate is recommended as part of the Ventilator Care Bundle to reduce bacterial colonization and decrease the risk of VAP. To describe the implementation of oral hygiene using 0.2% chlorhexidine gluconate as a nursing intervention for preventing Ventilator-Associated Pneumonia in mechanically ventilated patients with pneumonia admitted to the Intensive Care Unit of RS X. A descriptive case study was conducted involving two mechanically ventilated patients diagnosed with pneumonia. Data were collected through family interviews, clinical observation, physical examination, medical record review, and assessment using the Clinical Pulmonary Infection Score (CPIS). Oral hygiene with 0.2% chlorhexidine gluconate was performed twice daily for three consecutive days according to the ICU standard operating procedure. The first patient demonstrated improved oral hygiene, decreased tracheal secretions, negative sputum culture, and a CPIS of 3, indicating a low risk of VAP. The second patient also showed improvement in oral hygiene; however, the CPIS remained 8 due to bronchopneumonia with Acute RespiratoryDistress Syndrome (ARDS), severe oxygenation impairment, and persistent pulmonary inflammation. These findings suggest that oral hygiene contributes to maintaining oral cleanliness and reducing bacterial colonization, although its effectiveness in reducing VAP risk is influenced by disease severity and the patient's clinical condition. Oral hygiene using 0.2% chlorhexidine gluconate is an effective nursing intervention for maintaining oral hygiene as part of VAP prevention. However, optimal outcomes require comprehensive implementation of the Ventilator Care Bundle and appropriate management of other clinical factors associated with VAP.